The Derveni papyrus : unearthing ancient mysteries - Santamaría Álvarez, Marco Antonio (Papyrologica Lugduno-Batava, 2019)
The Derveni Papyrus: Unearthing Ancient Mysteries is devoted to this fascinating and challenging document, discovered in 1962 in a tomb in Derveni, near Thessaloniki, and dated c. 340-320 BCE. It contains a text probably written at the end of 5th c. BCE, which after some reflections on minor divinities and unusual cults, comments upon a poem attributed to Orpheus from an allegorical and philosophical perspective. This volume focuses on the restoration and conservation of the papyrus, the ideas of the anonymous author about Erinyes and daimons, the quoted Orphic poem in comparison with Hesiod's Theogony and Parmenides' poem, the exegetical approach of the commentator, his cosmogonic system, his attitude regarding mystery cults and his peculiar theology.